Power and exploitation in the Czech lands in the 10th-12th centuries : a Central European perspective - Petráček, Tomáš, 1972-; Miller, Sean Mark, 1968- (Leiden : Brill, 2017)
Power and Exploitation in the Czech Lands in the 10th-12th Centuries: A Central European Perspective offers a unique analysis of the history of early medieval Czech society. It draws new attention to the role of serfdom and slavery in the early period of the Přemyslid dynasty in the Czech lands, and the organization of land and property access and ownership. The provocative conclusions reached by the author in this study shed new light on the oldest period of Czech history. Petráček analyses these issues comparatively, also taking into account Poland and Hungary; this is an approach unique to this book.
1, Introduction -- 2, Overview of the research -- 3, Donated people in social and economic contexts -- 4, Free strata of the agricultural population -- 5, Donated people and the economy of the Přemyslid state -- 6, Bohemian society in the Central European context -- 7, Conclusion -- 8, Appendix: Donated people in the written sources
Obsahuje bibliografické odkazy a rejstřík
Elektronická reprodukce.
Keywords: 10.-12. století; středověká společnost -- Česko -- 10.-12. století; nižší společenské třídy -- Česko -- 10.-12. století; nevolníci -- Česko -- 10.-12. století; nevolnictví -- Česko -- 10.-12. století; medieval society -- Czechia -- 10th-12th centuries; serfdom -- Czechia -- 10th-12th centuries; serfs -- Czechia -- 10th-12th centuries; social classes -- Czechia -- 10th-12th centuries; social structure -- Czechia -- 10th-12th centuries; Česko -- sociální poměry -- 10.-12. století; Česko -- dějiny -- 10.-12. století; Czechia -- social conditions -- 10th-12th centuries; Czechia -- history -- 10th-12th centuries; e-knihy online; monografie; e-books online; monographs; Přemyslovci (rod)